MRP8/14 serum levels as diagnostic markers for systemic juvenile idiopathic arthritis in children with prolonged fever. (24th September 2021) - Park, Carolin; Miranda-Garcia, María; Berendes, Rainer; Horneff, Gerd; Kuemmerle-Deschner, Jasmin; Ganser, Gerd; Huppertz, Hans-Iko; Minden, Kirsten; Haas, Johannes-Peter; Jansson, Annette F; Borte, Michael; Schuetz, Catharina; et al.
Abstract: Objectives: Differential diagnosis in children with prolonged fever is challenging. In particular, differentiating systemic-onset JIA (SJIA) from infectious diseases is difficult. Biomarkers are needed that support the diagnostic work-up. The aim of this study was to validate the usefulness of Myeloid-related protein 8/14 (MRP8/14) measurements in the diagnostic work-up of febrile children and to transfer it to clinical practice. Methods: Data for 1110 paediatric patients were included and divided into two cohorts: (cohort A) for validation of MRP8/14 test performance with three different testing systems: the experimental ELISA, commercial ELISA and an innovative (point-of-care test) lateral flow immunoassay (LFIA); (cohort B) to validate the diagnostic accuracy with the two latter assays. Results: In cohort A ( n  = 940), MRP8/14 was elevated in SJIA (12 110 ± 2650 ng/ml mean ± 95% CI) compared with other diagnoses (including infections and autoinflammatory diseases; 2980 ± 510 ng/ml) irrespective of fever and anti-inflammatory treatment ( P  < 0.001). In untreated patients with fever ( n  = 195) MRP8/14 levels in SJIA (19 740 ± 5080 ng/ml) were even higher compared with other diagnoses (4590 ± 1160 ng/ml) ( P  < 0.001, sensitivity 73%, specificity 90%). In group B1, the performance of the tests was confirmed in untreated patients with fever ( n  = 170): commercial ELISA (sensitivity 79%, specificity 89%) and LFIA (sensitivity 84%, specificity 81%). Compared with ferritin, IL-18, ESR, soluble IL-2 receptor and procalcitonin, MRP8/14 showed the best accuracy. Conclusion: MRP8/14 serum analyses have been validated as a helpful tool supporting the diagnosis of SJIA in febrile children. The results could be confirmed with commercial ELISA and LFIA enabling a rapid diagnostic point-of-care screening test.